iNEMO : a multi-sensor real-time human activity monitoring system - Mi, Ding. (2013)
With the campus competition held by ST Microelectronics, the iNEMO sensor is a unique evaluation and development tool that offers up to 10 degrees of freedom, using combinations of 3-axis linear acceleration, angular rate and motion sensing, managed by an STM32 32-bit microcontroller and would be designed for such kind of innovative project to fulfill the modern technology application.